O impacto do processo de mudança organizacional com introdução de uma nova cultura nas percepções e atitudes dos funcionários: o caso de uma instituição de ensino de idiomas - Migliora, Maria Eduarda Proença P. (2018)
Purpose: his study aims to understand, from an exploratory approach within the context of an acquisition operation of a Brazilian language education company, the impacts of an organizational change in the perception and attitude of the employees. Design/Methodology/Approach: We used a qualitative exploratory approach. The context of this paper is the acquisition of language education company in Brazil. We used references from organizational cultures and organizational change theories as background for the analysis. Ten employees were interviewed through open questions and the results were found by the content analysis method. We discovered two final categories and thirteen subcategories. Findings: As a conclusion, it was possible to understand this phenomenon from the perspective of these collaborators, through the schematization of the employees’ perspective of the organizational change and its effects on their motivation, sense of belonging, coordination and the impact on the organization and its results. Research limitations: The main limitation of the study is the active participation of the author on the context of this study, which can, not intentionally alter some of the interpretations of the interview. Practical implications: The categories found can be used in other studies regarding the same subject. In management practice, the study may help future acquisition operations as it raises relevant impacts of the organizational change for the group of employees within this context. It can also be useful as background for the conception for organizational change plans built by the companies going through the same situation